Wakaf Ahli: Dinamika Kebijakan Negara dan Sistem Pelaksanaannya di Malaysia - Ayatina, Haerini (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Dzurri waqf is also called waqf expert which is intended for family members, is an asset or a benefit that is waqf and managed by certain groups, namely the family or close relatives of the waqif (waqif) with the aim of public interest and benefit. Waqf experts are connected with Islamic family law. Waqf experts are able to help the waqif hand over assets to his family and descendants. The existence of the implementation of waqf experts is practiced by friends, such as Umar bin Khattab's waqf for his descendants and Uthman bin Affan's waqf. This article discusses policies and regulations from a legal standpoint and the implementation of waqf experts in institutions and institutions in Malaysia. Although relatively small, waqf management experts in Malaysia face difficulties in terms of rules and regulations. This study used a qualitative literature review method, then the data were analyzed systematically. The results show that the Majlis Religion of Islam and Malay Customs implemented waqf experts in Malaysia State of Kelantan in 1921. The specialty when implementing dzurri waqf is to guarantee the continuity of the benefits felt by family members as beneficiaries. The good thing about this is that the benefits produced grow and develop well for the good of mauquf alaih and the good of society. In addition, expert waqf management experts need to improve it in order to encourage its implementation in the future.